Dynamic characteristics modelling and analysis for dry screw vacuum pumps. (April 2022) - Li, Dantong; He, Zhilong; Sun, Shizhong; Xing, Ziwen
Abstract: This paper modeled the dynamic characteristics of dry screw vacuum pumps considering the forces induced by gas, gear, bearings, and rotor gravity, and discussed the load on bearings and gear comprehensively employing the proposed model. First, the balance equations on force and torque were proposed based on a simplified force analysis model for a test dry screw vacuum pump. Next, the detailed calculation methods of gas force, gear load, bearing load, and motor power were presented, respectively. Furthermore, the calculated motor power was verified by comparing the measured results from a test experiment. Finally, the gas force, gear load, bearing load, and bearing power loss under different inlet pressures was discussed comprehensively. Results showed that the proposed model could effectively analyze the load and power distribution for dry screw vacuum pumps. The torque of synchronous gear could be reduced by reasonably selecting the driving shaft. The axial gas force acting on the end face of rotors showed the main contribution for the power loss of bearings, which accounted for up to 3.2% of total input power. The obtained conclusions could guide the reasonable design and selection of the supporting and driving components for dry screw vacuum pumps. Graphical abstract: Image 1 Highlights: The dynamic characteristic of dry screw vacuum pumps was modeled and analyzed. The forces induced by working gas, gear, bearings, and gravity were considered. The model was verified by comparing the simulated and experimental motor power. The gear load could be reduced by reasonably selecting the driving shaft. The bearing power loss accounted for up to 3.2% of total input power.